RELATIONS OLD FISHING TRIP , FLEET SIZE , SIZE MACHINE , AND AGE OF TOTAL ENGINE FUEL OIL BRING THE HAND AND LINE VESSEL AT OCEAN FISHING PORT BELAWAN NORTH SUMATERA - Susanti, Ester Desi; Zain, Jonny; ', Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted on 17 April – 07 may 2015 in PPS Belawan,provence North Sumatera. The purpose of this study was to find the relationshipbetween the fishing trip , the fleet size , engine size and age of the machine to theamount of fuel that will be taken when operating fishing vessels. The method usedis a survey method . A total of 27 units of fishing boats fishing (hand and line)sampled the same engine brand Mitsubishi . To see the relationship fishing trip ,the fleet size , engine size and age of the machine to the amount of fuel carriedaboard the fishing rod back and forth (hand and line) used multiple linear statistics. Results of this study showed that the relationship of the amount of fuel ( Y ) isbrought to the size of the fleet ( X1 ) , the size of the engine ( X2 ) , and the life ofthe engine ( X3 ) is Y = 68.71 to 6.43 ( X1 ) +1.4 ( X2 ) -1.22 ( X3 ) . theinfluence of the independent variable on the dependent variable was 18.2 %Keywords: Fishing Trip, Machine, boats fishing